Gallic acid induces T-helper-1-like Treg cells and strengthens immune checkpoint blockade efficacy. Issue 7 (11th July 2022) - Deng, Biaolong; Yang, Biaolong; Chen, Jieqiong; Wang, Shuaiwei; Zhang, Weiqi; Guo, Yixian; Han, Yichao; Li, Hecheng; Dang, Yongjun; Yuan, Yaqin; Dai, Xueyu; Zang, Yuansheng; et al.
Abstract : Background: Foxp3 + regulatory T (Treg ) cells facilitate tumor immune evasion by forming a suppressive tumor microenvironment. Therefore, immune therapies promoting Treg fragility may greatly enhance immune checkpoint blockade (ICB) efficacy in cancers. Methods: We have screened 2640 compounds and identified the gut microbial metabolite gallic acid, which promotes Foxp3 degradation and Treg instability by repressing Usp21 gene transcription. In vivo and in vitro experiments have been performed to explore the roles of Usp21 in Treg cells. Importantly, we treated tumor-bearing mice with gallic acid and anti-PD-1 antibody to explore the potential therapeutic value of gallic acid in clinical cancer immunotherapy. Results: Mechanistically, gallic acid prevents STAT3 phosphorylation and the binding of phosphorylated STAT3 to Usp21 gene promoter. The deubiquitinated Usp21 and stabilized PD-L1 proteins boost the function of Treg cells. Combination of gallic acid and anti-PD-1 antibody, in colorectal cancer (CRC) treatment, not only significantly dampen Treg cell function by impairing PD-L1/PD-1 signaling and downregulating Foxp3 stability, but also promote CD8 + T cells' production of IFN-γ and limited tumor growth. Conclusion: Our findings have implications for improving the efficacy of ICB therapy in CRC by inducing T-helper-1-like Foxp3 lo Treg cells.